Electrolyte Evolution: A Roadmap from Solvation Structure to Next-Generation Batteries - Li, Chengfeng; Chen, Xiangyu; Zhao, Lingfei; Lei, Yaojie; Yang, Zhuo; Zhu, Kunjie; Liu, Hua‑Kun; Dou, Shi‑Xue; Wang, Yun‑Xiao (Nano-Micro Letters, 2026)
Driven by global strategies for decarbonization and carbon neutrality, renewable-energy intermittency underscores the importance of large-scale electrochemical energy storage (EES). Rechargeable batteries, as the core components within EES, have long been restricted by limitations intrinsic to conventional dilute electrolytes, including narrow electrochemical stability windows, poor low-temperature performance, high flammability, and weak compatibility with high-voltage electrodes. Regulation of solvation structure in electrolytes has emerged as a key approach to overcome these bottlenecks. This review highlights five representative strategies: highly concentrated electrolytes, localized high-concentration electrolytes, weakly solvating electrolytes, hydrogen-bond regulated electrolytes, and eutectic electrolytes. These strategies have greatly advanced Li-ion, Na-ion, Zn-ion, Li–S, Li–air, and Na–S batteries. Finally, challenges ahead and opportunities in solvation-structure design are summarized to guide innovative and sustainable progress in next-generation energy storage technologies. Highlights: 1 This review elucidates how innovative electrolytes (highly concentrated electrolytes, localized high-concentration electrolytes, etc.) reshape ion–solvent interactions. 2 Solvation-structure regulation is highlighted as the key to enhanced battery performance, with its recent advances summarized across diverse battery systems. 3 This review outlines challenges and opportunities in solvation-structure design to guide next-generation energy storage technologies.